PRECONDITIONS FOR CHOOSING ONLINE STUDIES IN LATVIA - Lace, Alisa; Usca, Svetlana (Education Reform: Education Content Research and Implementation Problems, 2022)
After the Covid-19 pandemic, when every educational facility switched to studying from a distance, online studies have become available in practically any area. At the moment, the restrictions are reduced, and more opportunities to choose between online, offline and mixed education have become available. The goal of this research is to identify and describe the tendencies of choosing online studies for adult education in Latvia. The following questions are viewed in this research: Which factors affect the tendency to choose online studies for adult education? What are the correlations between the respondent profiles (age, marital status, previous education, etc.) and the affecting preconditions for choosing online education? During the research, 131 respondents from the entire country filled a form and participated in a survey, which was available online. The statistical data processing was done using the Kruskal-Wallis test, the Spearman’s correlation and descriptive statistics.